Circular concrete‐filled dual steel columns with ultrahigh‐strength concrete. Issue 4 (November 2016) - Romero, Manuel L.; Albero, Vicente; Espinós, Ana; Hospitaler, Antonio; Pons, David; Portolés, José M.; Ibañez, Carmen
Abstract: This paper presents the results of an experimental campaign in which the buckling resistance of 12 concrete‐filled dual steel columns was ascertained. Whereas some papers in the literature describe investigations into concentrically loaded stub columns with such typology, no investigations of slender columns have been found to date. The tests presented in this paper are the preliminary results of an extensive experimental campaign (28 tests) that analysed the effects of two parameters: strength of concrete (normal‐ and ultrahigh‐strength concrete) and the ratio between the thicknesses of the inner and outer steel tubes. A numerical model was also developed and validated, which helps further investigations. The buckling load of the specimens at room temperature is analysed in terms of the strength of the concrete and the appropriate distribution of the steel in the composite column. By maintaining the same total area of steel, two combinations were initially studied: "thick outer tube–thin inner tube" and "thin outer tube–thick inner tube". Finally, a discussion about the Eurocode 4 simplified method for composite columns, applied to these innovative specimens, is presented and shows unreliable results. Therefore, further tests would be needed to assess accurately the Eurocode 4 simplified method.